2017
DOI: 10.1209/0295-5075/120/10006
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of fermions in a d-dimensional box near a hard wall

Abstract: We study N noninteracting fermions in a domain bounded by a hard wall potential in d ≥ 1 dimensions. We show that for large N , the correlations at the edge of the Fermi gas (near the wall) at zero temperature are described by a universal kernel, different from the universal edge kernel valid for smooth potentials. We compute this d dimensional hard edge kernel exactly for a spherical domain and argue, using a generalized method of images, that it holds close to any sufficiently smooth boundary. As an applicat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
75
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 30 publications
(82 citation statements)
references
References 35 publications
7
75
0
Order By: Relevance
“…Pursuing this analogy with random matrices, one may wonder whether one can define a "density" associated to this point process that would capture the existence of these edge regions, and would be the equivalent of the Wigner semi-circle in random matrix theory. This is left for future investigations [46]. which is clearly different from the scaling function found at the edge [20] (corresponding to the limit α → 0), given in Eq.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Pursuing this analogy with random matrices, one may wonder whether one can define a "density" associated to this point process that would capture the existence of these edge regions, and would be the equivalent of the Wigner semi-circle in random matrix theory. This is left for future investigations [46]. which is clearly different from the scaling function found at the edge [20] (corresponding to the limit α → 0), given in Eq.…”
Section: Resultsmentioning
confidence: 58%
“…What happens for heavy tailed jump distributions, i.e. the case of Lévy flights, remains a challenging open question, in particular because we do not know how to solve the backward integral equations (45) and (46) in this case. We hope that the results obtained here will motivate further works to develop alternative methods to study the gap statistics of Lévy flights.…”
Section: Resultsmentioning
confidence: 99%
“…Another interesting feature of the case d > 1 concerns the large deviations of r max (T ). Indeed, it was shown in [235,236] that, at variance with the standard scenario (94) found for instance for the β-Gaussian ensembles, there exists generically an intermediate regime of fluctuations between the typical and the left large deviation regime. This intermediate regime, which is actually not restricted to EVS but also concerns other observables like the full counting statistics [237], seems to be a rather generic feature of higher dimensional determinantal processes, including in particular (complex) Ginibre random matrices and two-dimensional Coulomb gas [238].…”
Section: Extreme Statistics Of Trapped Fermionsmentioning
confidence: 84%
“…The statistics of the maximal radial distance r max (T ) of the fermions from the trap center was also studied in dimension d > 1, both for smooth potentials like the harmonic well [232], and the hard box (spherical) potential [235,236]. In both cases, although the positions of the fermions are strongly correlated at T = 0, it was found that, for large N , the statistics of r max (T = 0) is given by the EVS of IID random variables, i.e.…”
Section: Extreme Statistics Of Trapped Fermionsmentioning
confidence: 99%
“…It is natural to ask the question if there exist quantum potentials that correspond to the general JUE with arbitrary parameters a and b. Indeed, it was shown recently [38] that a potential of the type…”
Section: Hard Box Potential and The Juementioning
confidence: 99%